Existential Regret: A Crossroads of Existential Anxiety and Existential Guilt (Existential Analysis: Journal of the Society for Existential Analysis, 2005)
This article examines the experience of existential regret, defined as a profound desire to go back and change a past experience in which one has failed to choose consciously or made a choice that did not follow one's beliefs, values or growth needs.